(untitled) (The Pakistan Development Review, 2020)
The Pakistan Institute of Development Economics (PIDE) organised a conference on the development policy of Pakistan with a focus on planning and public investment policy. At the Conference, a PIDE study entitled, Doing Development Better1 was launched and discussed. The key findings of the conference are listed below: